The Arab-Israeli conflict - Kumaraswamy, P. R., author.
1 online resource
Keywords: "This book provides a holistic view of the conflict between Israel and its Arab neighbours and studies the global implications of their fraught relations. Focusing on the conflict from its beginning in the late 19th Century, the author provides a well-rounded and balanced narrative by examining its religious, ideological, ethnic, political, national, regional and international dimensions. The volume covers a wide range of issues such as the conflicting historical legacy of the city of Jerusalem, Jewish longing for a homeland, the partition of Palestine, various wars and conflicts since 1948, Palestinian resistance, Arab Boycott of Israel and the Abraham Accords. It also tackles the contested national claims and the refugee question and looks at various peace-making efforts, including the role of external stakeholders such as the US, UK, Russia and India. A comprehensive study of the Arab-Israeli conflict, the book is richly supported by a swath of references to materials, documents, maps and video links. It will be an essential reading for students, academics, and teachers of politics and international relations, national security, geopolitics, history, military and strategic studies, Middle East studies, conflict resolution and peace-making"--